Gingival spatial analysis reveals geographic immunological variation in a microbiota-dependent and -independent manner - Yasmin Jaber; Avital Sarusi-Portuguez; Yasmin Netanely; Reem Naamneh; Shahd Yacoub; Or Saar; Nadeem Darawshi; Luba Eli-Berchoer; Hagit Shapiro; Eran Elinav; Asaf Wilensky; Avi-Hai Hovav (npj Biofilms and Microbiomes)
Abstract In mucosal barriers, tissue cells and leukocytes collaborate to form specialized niches that support host-microbiome symbiosis. Understanding the spatial organization of these barriers is crucial for elucidating the mechanisms underlying health and disease. The gingiva, a unique mucosal barrier with significant health implications, exhibits intricate tissue architecture and likely contains specialized immunological regions. Through spatial transcriptomic analysis, this study reveals distinct immunological characteristics between the buccal and palate regions of the murine gingiva, impacting natural alveolar bone loss. The microbiota primarily affects gingival immunity in the buccal region. Additionally, a significant influence of the microbiota on the junctional epithelium facing the oral biofilm offers new insights into neutrophil recruitment. The microbiota also regulates the proliferation and barrier-sealing function of the gingival epithelium. This underscores the presence of immunological niches in the gingiva, with the microbiota differentially influencing them, highlighting the high complexity of this oral mucosal barrier.